Importancia de la elaboración del humus de la lombriz californiana en el cultivo de tomate (Solanum lycopersicum). - Zambrano Sánchez, Ana Meilyn (2022)
This bibliographic research details the importance of the elaboration of the humus of the Californian worm in the cultivation of tomato (Solanum lycopersicum). The use of this organic fertilizer in the aforementioned crop helps in its growth, it also gives better consistency to the fruit improving its production, it also prevents the appearance of chlorosis and the different pests that affect the tomato crop since it has energy sources that improve its development phases because this fertilizer obtains high levels of nutrients that are easy to assimilate for plants. The information was collected through virtual libraries, updated texts, journals and articles, presentations, congresses and all bibliographic material of a scientific nature that contributes to the development of this documentary research. The results and conclusions obtained in this research were favorable since it describes the elaboration of the humus of the Californian worm, its benefits and importance when applying it in tomato cultivation; it should be noted that this fertilizer gives optimal productive yields in the aforementioned crop.